Implementasi Pelatihan Manajemen Media Sosial di SMK Negeri 2 Sekotong - Sutarini, Ida Ayu; Maulida, Novita; Amy, Najamuddin (Jurnal Gema Ngabdi, 2025)
Sekotong Beach is located in West Lombok, West Nusa Tenggara. This area offers marine tourism with coral reefs and diverse marine life, however this destination is less popular compared to other destinations on Lombok Island. The Communication Studies Department at University of Mataram collaborates with SMK Negeri 2 Sekotong to raise awareness among domestic and foreign tourists about the beauty of Sekotong Beach, thereby encouraging economic growth in the local community. The purpose of the Community Service Program (PkM) is to train students of SMK Negeri 2 Sekotong in maximizing the use of social media to promote tourist destinations in Sekotong. This PkM activity begins with a preliminary study, training, evaluation, and reporting. This event was attended by 30 students from the Hospitality, Culinary Arts, and Travel Business Departments. The training materials consist of an introduction to social media, social media strategy planning, and creating engaging content. At the end of the session, the committee concluded with the distribution of feedback questionnaires to the participants. The results of the questionnaire distribution will be used as evaluation material for the next PkM activities. The outcome of this training activity is that the students acquired skills in managing social media to enhance their ability to market tourist destinations.